Hydroxyapatite Based Material: Natural Resources, Synthesis Methods, 3D Print Filament Fabrication, and Filament Filler - Lulu Sekar Taji; Deden Eko Wiyono; Achmad Dwitama Karisma; Agus Surono; Eva Oktavia Ningrum (Institut Teknologi Sepuluh Nopember, 2022)
Hydroxyapatite is a biomaterial that has been recognized in terms of hard tissue engineering due to its similarity in composition to bioapatite. Moreover, abundant resources and diverse synthesis methods make hydroxyapatite easy to produce. The application in terms of 3D print-based network engineering is also being intensively explored due to hydroxyapatite scaffold fabrication process flexibility. In this review, various hydroxyapatite from natural sources, synthesis methods, hydroxyapatite-based 3D print filament fabrication techniques, as well as fillers used in the production of filaments are discussed.